2019
DOI: 10.1016/j.cub.2018.11.058
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Propagation of Signals and Nutrients in Fungal Networks via Specialized Hyphae

Abstract: Graphical AbstractHighlights d Transport of signals and nutrients in fungal mycelia occurs via specialized hyphae d Transport in these hyphae is bidirectional d Direction of transport in these hyphae oscillates between acropetal and basipetal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 55 publications
2
50
0
Order By: Relevance
“…Evolutionarily speaking, this proposed mechanism is intermediate between the cytoskeleton-mediated mechanosensing of mammalian cells and cell wall-reliant mechanosensing of bacteria and plants, particularly related to osmolarity stress and loss of turgor pressure. In fact, fungal hyphae have been observed to grow in an oscillatory manner and bidirectionally transmit signals tied to pathogen attack and nutrient sources (Schmieder et al, 2019). Physarum may have optimized this inherent ability to execute information processing more rapidly.…”
Section: Computational Modeling Of Mass Sensingmentioning
confidence: 99%
“…Evolutionarily speaking, this proposed mechanism is intermediate between the cytoskeleton-mediated mechanosensing of mammalian cells and cell wall-reliant mechanosensing of bacteria and plants, particularly related to osmolarity stress and loss of turgor pressure. In fact, fungal hyphae have been observed to grow in an oscillatory manner and bidirectionally transmit signals tied to pathogen attack and nutrient sources (Schmieder et al, 2019). Physarum may have optimized this inherent ability to execute information processing more rapidly.…”
Section: Computational Modeling Of Mass Sensingmentioning
confidence: 99%
“…Perhaps, filamentous fungi can perceive the sound of hyphal grazers. There would be advantages of vibration detection as a warning signal: the fungal mycelium could avoid advancing into areas of intense animal activity, for example of collembola or earthworms (the distribution of animals in soil tends to be quite clustered), or the fungus could mount defense-related actions (induced defense) when it encounters an impending attack by microarthropods or nematodes [10]. Beyond avoidance in space and upregulation of defense, a third possible fungal response to sound could be increased sporulation.…”
Section: How Sound Might Carry Useful Information For Soil Biotamentioning
confidence: 99%
“…However, the response rapidly spread from those chambers, recruiting the whole fungus into a network-wide response. This response didn't travel along every hypha, however, but was confined to a few hyphae (which Schmieder et al [7] identified as a special class of propagating hyphae), on which the signal traveled at a speed of about 5 mm/s. Even more remarkably, signals did not simply travel toward the edge of the network, but also traveled (at similar speeds!)…”
mentioning
confidence: 99%
“…Previous work from Markus Kü nzler's group showed that, when nematodes graze upon C. cinerea, the fungus responds by releasing a host of chemical weapons [6]. Now, in a new study published recently in Current Biology, this group has shown how the whole fungal network is mobilized to produce these chemical defenses [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation